An evaluation of the audiovisual media program of the Far Eastern University - Mendoza, Digna Medina (1975)
The purpose of this study is to evaluate the organization and operation of the educational media program of the Far Eastern University and to deduce on the basis of such evaluation certain implications for the university administration. Specifically, the research seeks to determine the present status of the educational media program of the Far Eastern University in accordance with: administrative commitment, media services-curriculum and instruction, media services center, facilities, budget and finance, and staff.
Thesis (M.Ed.)--University of the Philippines
Keywords: Audio-visual education -- Philippines